Properties of Human Embryonic Stem Cells and Their Differentiated Derivatives Depend on Nonhistone DNA-Binding HMGB1 and HMGB2 Proteins - Bagherpoor, Alireza Jian; Dolezalova, Dasa; Barta, Tomas; Kučírek, Martin; Sani, Soodabeh Abbasi; Ešner, Milan; Kunova Bosakova, Michaela; Vinarský, Vladimír; Peskova, Lucie; Hampl, Aleš; Štros, Michal (Stem cells and development, 2017)
HMGB1 and HMGB2 proteins have been implicated in numerous cellular processes, including proliferation, differentiation, apoptosis, and tumor growth. It is unknown whether they are involved in regulating the typical functions of pluripotent human embryonic stem cells (hESCs) and/or those of the differentiated derivatives of hESCs. Using inducible, stably transfected hESCs capable of shRNA-mediated knockdown of HMGB1 and HMGB2, we provide evidence that downregulation of HMGB1 and/or HMGB2 in undifferentiated hESCs does not affect the stemness of cells and induces only minor changes to the proliferation rate, cell-cycle profile, and apoptosis. After differentiation is induced, however, the downregulation of those proteins has important effects on proliferation, apoptosis, telomerase activity, and the efficiency of differentiation toward the neuroectodermal lineage. Furthermore, those processes are affected only when one, but not both, of the two proteins is downregulated; the knockdown of both HMGB1 and HMGB2 results in a normal phenotype. Those results advance our knowledge of regulation of hESC and human neuroectodermal cell differentiation and illustrate the distinct roles of HMGB1 and HMGB2 during early human development.
Keywords: buněčná diferenciace; protein HMGB2; Humans; buněčný rodokmen; telomerasa; tvar buňky; histony; Cell Cycle; Down-Regulation; HMGB2 Protein; HMGB1 Protein; Telomerase; Cell Self Renewal; lidé; Neural Plate; lidské embryonální kmenové buňky; proliferace buněk; Cell Lineage; down regulace; protein HMGB1; apoptóza; neurální ploténka; buněčné linie; transfekce; Cell Line; Cell Shape; Cell Proliferation; Histones; Cell Differentiation; Transfection; Human Embryonic Stem Cells; buněčná sebeobnova; buněčný cyklus; Apoptosis